STRATEGI PENGUSAHA WARUNG KOPI DALAM MEMPERTAHANKAN EKSISTENSINYA DI KOTA KENDARI - Suardi Suardi; Wa Ode Sitti Hafsah; Ashmarita Ashmarita (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
This study aims to find out about the existence and strategy of coffee shops in Kendari City. This research uses the adaptation strategy theory by J.W Bennet. The method of this study is the ethnographic method. Collecting data is observation and in-depth interviews. Analysis data is analyzed descriptive qualitative. The results of the study show that doing a culinary business in Kendari City is a very promising business option. One of them is a coffee shop business that turned out to be able to generate substantial profits even though it only issued a capital that was not too large. The popularity of coffee shops today is also supported by the lifestyle of urban people who are very fond of spending their free time in a coffee shop for various reasons for visiting. Some strategies used by coffee shop entrepreneurs in maintaining the existence of their businesses such as (a) providing good facilities and services; (b) determination of the location of the coffee shop business; (c) determine affordable menu prices.